Learner and Functionary Response to Adult Literacy Programs in India: A Case of Uttarakhnad State - JOSHI, S. B.; BOHRA, N. S. (Journal of Research in Educational Sciences; Vol 10 No 12 (2019): JRES Volume X Issue 12 Winter 2019DO - 10.14505//jres.v10.12.02, 2020)
This study measuring the responses of learners and functionaries to the adult literacy programs in India and Uttarakhnad an Indian state is taken as model case. In-depth unstructured interviews and participant-observation is used. Having studied extensively various reports, articles, journals and survey data it is pertinent to suggest an effective model of adult education that is executable, desirable, acceptable, functional, result oriented which can be monitored and tracked frequently. To address these requirements “Technologically Inclusive Adult Education (TIAE)” has been suggested.